Factors of Product Customization for the 1200cc Passenger Car Segment: An Empirical Study in Central India - Jain, Neeraj Kumar; Thakar, G. D. (Indian Journal of Marketing, 2014)
Increasing competition in the automobile market has put a great challenge before car companies to cater to the specific needs of the customers in order to remain in business. The growing competition also requires frequent innovations in the industry. High cost associated with frequent innovations may cause big setbacks to these companies if any new launch of a passenger car model fails to attract the customers' attention. A precise model specification, catering to the needs and aspirations of the customers, is ,therefore, required. This paper is an effort to find out the factors that help the companies to customize their products as per varied customer needs, categorized on the basis of their socioeconomic classes such as age, city, occupation, income group, and their present car ownership status. The study investigated selected twenty variables as determinants of the customers' choice for the selection of a 1200cc car. Factor analysis (on the influencing variables) out of the said twenty variables was applied to the respective categories of customers. The analysis found varying factors that contributed differently in the customers' choice while selecting a 1200cc car. Considering these factors and their contribution, the passenger car companies, especially in the 1200cc segment, can incorporate appropriate specifications for innovation in their products.